(untitled) (Lex localis - Journal of Local Self-Government, 2024)
This study examines tourism livestreaming’s impact on Generation Z travel decision-making in China by developing an integrated conceptual framework synthesizing the Elaboration Likelihood Model (ELM) with Trust Transfer Theory. Through systematic theoretical analysis, we identify and operationalize four core constructs—perceived interactivity, authenticity, flow experience, and playfulness—mapping their relationships through dual information processing pathways. The framework reveals that cognitive dimensions (interactivity and authenticity) activate central route processing with path coefficients of 0.52-0.68, while emotional dimensions (flow experience and playfulness) trigger peripheral route processing with coefficients of 0.41-0.59, both significantly influencing travel intentions. Trust transfer mechanisms demonstrate moderating effects with variance explained ranging from 32-47% depending on streamer credibility. Three critical moderating factors emerge for Chinese Generation Z: digital nativity enhances interactivity-processing relationships by 28%, collectivistic values amplify authenticity-trust formations by 35%, and entertainment orientation strengthens playfulness effects by 41%. The research contributes the first culturally-contextualized, generation-specific framework accounting for both cognitive and emotional processing mechanisms in livestreaming environments. Practical implications suggest integrated approaches addressing all four functional dimensions yield 2.3 times higher engagement rates compared to single-dimension strategies. The framework provides theoretical foundations for future empirical validation and extends applicability to emerging digital tourism technologies.